2017
DOI: 10.9755/ejfa.2016-12-1975
|View full text |Cite
|
Sign up to set email alerts
|

Plough Pan Impacts Maize Grain Yield, Carbon Assimilation, and Nitrogen Uptake in the Corn Belt of Northeast China

Abstract: This study aims to investigate the responses of carbon assimilation, grain yield, leaf stay-green rate, nitrogen uptake and distribution to soil compaction in the hard plow pan caused by repeated use of tractor-driven cultivator in Northeast China. The typical hybrid maize variety “Zhengdan 958” was exposed to two treatments of simulated plow pan (SP) and simulated subsoiling (SS, control) in pot experiments from 2012 to 2014. Compared with SS, SP significantly reduced net photosynthetic rate (Pn) during growt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 26 publications
0
7
2
Order By: Relevance
“…2A, 3A, and 3B). Despite high grain yield, N uptake levels at silking and post-silking in our study were less than the levels reported in previous studies Liu et al, 2014b;Mu et al, 2015;Zheng et al, 2016;Cao et al, 2017;Zhou et al, 2017). Furthermore, we found that the slope of the relationship between N uptake post-silking and maize grain yield (y = 13.254e 0.151x ) was greater than that of N uptake at silking and grain yield (y = 10.583x + 19.584), and thus the N uptake post-silking may be more important (Mueller and Vyn, 2016).…”
Section: Discussion Nitrogen Uptake and Grain Yieldcontrasting
confidence: 92%
See 1 more Smart Citation
“…2A, 3A, and 3B). Despite high grain yield, N uptake levels at silking and post-silking in our study were less than the levels reported in previous studies Liu et al, 2014b;Mu et al, 2015;Zheng et al, 2016;Cao et al, 2017;Zhou et al, 2017). Furthermore, we found that the slope of the relationship between N uptake post-silking and maize grain yield (y = 13.254e 0.151x ) was greater than that of N uptake at silking and grain yield (y = 10.583x + 19.584), and thus the N uptake post-silking may be more important (Mueller and Vyn, 2016).…”
Section: Discussion Nitrogen Uptake and Grain Yieldcontrasting
confidence: 92%
“…In some studies, N uptake at maturity was >400 kg N ha −1 , and N uptake at silking and post-silking was >200 kg N ha −1 Guo et al, 2015), which are greater than that in our study. Despite high grain yield, N uptake levels at silking and post-silking in our study were less than the levels reported in previous studies Liu et al, 2014b;Mu et al, 2015;Zheng et al, 2016;Cao et al, 2017;Zhou et al, 2017). In previous reports, we found that N uptake at maturity, silking, and post-silking increased with improvement in grain yield ( Fig.…”
Section: Discussion Nitrogen Uptake and Grain Yieldcontrasting
confidence: 87%
“…This result is in agreement with earlier reports of Ceyhan et al (2008) in bean (Phaseolus vulgaris L.) and Fabijanac et al (2006), who demonstrated sowing date did not affect grain yield and protein content in any of the tested hybrids. Similar results of higher protein concentration with late of biomass stored in the stem and leaf during vegetative growth (Ning et al, 2013;Cao et al, 2017). Plant with delayed sowing shortened the growth periods of vegetative and reproductive growth, thus leading to a reduction of dry matter accumulation during growth stage.…”
Section: Grain Starch Protein Oil Content and Yieldmentioning
confidence: 53%
“…Nitrogen (N) content in seed grains is an important nutrition factor, which is highly associated with human health and animal feeding (Cao et al, 2017). It has been well-known that grain N accumulation is not only based on N uptake during the post-silking stage, but also closely related to the remobilization of N stored in leaf and stem during vegetative growth stage (Liu et al, 2016).…”
Section: Grain Test Weight and N Contentmentioning
confidence: 99%
See 1 more Smart Citation